Sosilaisasi Pencegahan Bullying di Sekolah Melalui Program “Sosialisasi Bahaya Bullying Bagi Mental Siswa” - Deni Sunaryo; Hamdan; Santi Octaviani; Yoga Adiyanto (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The younger generation is the foundation and capital of the nation's development. For this reason, parents, educators and the government are expected to seriously provide the best education for them. The reality is that all citizens, local governments, families and parents are obliged and responsible for providing protection and guaranteeing the fulfillment of children's human rights in accordance with their duties and responsibilities. Legal rules regarding bullying against children have been regulated by the State in the form of laws, meanwhile, a clear understanding of bullying is not yet owned by some adolescents both within the school environment and outside the school environment. Even though acts of bullying can harm other people and can even cause the loss of the future of a child who is a victim of this act. For this reason, the Serang Raya University Service Team is interested in carrying out community service activities for students of SMP Negri 2 Cikeusal Serang which in this case is given in the form of "Socialization of the Dangers of Bullying for Mental Students". using several methods including delivering material directly or lectures, sharing, discussions, questions and answers, and dialogue. The results obtained from the Socialization of the Dangers of Bullying for students' mentality are: the results of this dedication show that students' knowledge about stopping bullying increases, increase knowledge and understanding of legal regulations related to bullying, the impact of bullying.